The determinants of stock and bond return comovements - Lieven Baele; Geert Bekaert; Koen Inghelbrecht (National Bank of Belgium, 2007)
We study the economic sources of stock-bond return comovement and its time variation using a dynamic factor model. We identify the economic factors employing structural and non-structural vector autoregressive models for economic state variables such as interest rates, (expected) inflation, output growth and dividend payouts. We also view risk aversion, and uncertainty about inflation and output as additional potential factors. Even the best-fitting economic factor model fits the dynamics of stock-bond return correlations poorly. Alternative factors, such as liquidity proxies, help explain the residual correlations not explained by the economic models.
Keywords: G11; G12; G14; E43; E44; 330; factor models; stock-bond return correlation; macroeconomic factors; new-Keynesian models; structural VAR; liquidity; flight-to-safety; Kapitaleinkommen; Anleihe; Aktie; Korrelation; Portfolio-Management; CAPM; Welt